An experimental evaluation of helical piles as a liquefaction-induced building settlement mitigation measure. Issue 151 (December 2021) - Orang, Milad Jahed; Boushehri, Reza; Motamed, Ramin; Prabhakaran, Athul; Elgamal, Ahmed
Abstract: This study evaluates the application of helical piles to reduce liquefaction-induced foundation settlement and investigates their seismic performance in liquefiable grounds. Two large-scale shake table test series, one without mitigation and one using helical piles, were conducted using the shake table facility at the University of California, San Diego. Each model was extensively instrumented and subjected to two consistently applied shaking sequences. The experimental results indicated reduced excess pore-water pressure generation around the helical pile group, attributed mainly to the densification around the piles during installation. The foundation supported on helical piles underwent almost no foundation differential settlement and tilt. The post-shaking liquefaction-induced settlement mechanisms did not affect the helical pile foundation settlement. Although this study introduced helical piles as a reliable and highly efficient measure to mitigate liquefaction-induced foundation tilt and settlement, the proper design and application of helical piles still need thorough investigation due to possible amplified superstructure response. Highlights: Evaluated the performance of helical piles in liquefiable grounds. First of its kind large-scale shake table test on helical piles in liquefiable soils. Improved performance of shallow foundations underpinned by helical piles. Introduced helical piles as an effective foundation settlement mitigation measure.